Beckett's Art of the Commonplace: The 'Sottisier' Notebook and mirlitonnades Drafts. Issue 1 (April 2019) - Hulle, Dirk Van
Abstract : In the 1970s, Samuel Beckett wrote a set of short poems, called mirlitonnades . Explicitly conceived as minor or 'throwaway' poetry, the drafts of the mirlitonnades are jotted down on 'throwaway' material and everyday objects, such as envelopes, letters, a piece from a box of cigars, pages torn from notebooks and coloured notepads. This essay tries to map the genesis of these poems in order to understand the 'throwaway' gesture of the draft material. It foregrounds the 'everyday' materiality of the mirlitonnades manuscripts and argues that the use of these scraps of paper bears a relation to the content of the poems, in which 'death' is the most 'everyday' element. It is so omnipresent that it emanates from and takes shape in the most everyday objects.